Olig1 is required for noggin‐induced neonatal myelin repair. Issue 4 (April 2017) - Sabo, Jennifer K.; Heine, Vivi; Silbereis, John C.; Schirmer, Lucas; Levison, Steven W.; Rowitch, David H.
Abstract : Objective: Neonatal white matter injury (NWMI) is a lesion found in preterm infants that can lead to cerebral palsy. Although antagonists of bone morphogenetic protein (BMP) signaling, such as Noggin, promote oligodendrocyte precursor cell (OPC) production after hypoxic‐ischemic (HI) injury, the downstream functional targets are poorly understood. The basic helix‐loop‐helix protein, oligodendrocyte transcription factor 1 (Olig1), promotes oligodendrocyte (OL) development and is essential during remyelination in adult mice. Here, we investigated whether Olig1 function is required downstream of BMP antagonism for response to injury in the neonatal brain. Methods: We used wild‐type and Olig1 ‐null mice subjected to neonatal stroke and postnatal neural progenitor cultures, and we analyzed Olig1 expression in human postmortem samples from neonates that suffered HI encephalopathy (HIE). Results: Olig1 ‐null neonatal mice showed significant hypomyelination after moderate neonatal stroke. Surprisingly, damaged white matter tracts in Olig1 ‐null mice lacked Olig2 + OPCs, and instead proliferating neuronal precursors and GABAergic interneurons were present. We demonstrate that Noggin‐induced OPC production requires Olig1 function. In postnatal neural progenitors, Noggin governs production of OLs versus interneurons through Olig1 ‐mediated repression of Dlx1/2 transcription factors. Additionally, we observed that Olig1 and the BMP signaling effector, phosphorylated SMADs (Sma‐ and Mad‐related proteins) 1, 5, and 8, were elevated in the subventricular zone of human infants with HIE compared to controls. Interpretation: These findings indicate that Olig1 has a critical function in regulation of postnatal neural progenitor cell production in response to Noggin. Ann Neurol 2017;81:560–571